New contraceptive eligibility checklists for provision of combined oral contraceptives and depot-medroxyprogesterone acetate in community-based programmes - Amanda Stang; Pamela Schwingl; Roberto Rivera (The World Health Organization, 2000)
Community-based services (CBS) have long used checklists to determine eligibility for contraceptive method use, in particular for combined oral contraceptives (COCs) and the 3-month injectable contraceptive depot-medroxyprogesterone acetate (DMPA). As safety information changes, however, checklists can quickly become outdated. Inconsistent checklists and eligibility criteria often cause uneven access to contraceptives. In 1996, WHO produced updated eligibility criteria for the use of all contraceptive methods. Based on these criteria, new checklists for COCs and DMPA were developed. This article describes the new checklists and their development. Several rounds of expert review produced checklists that were correct, comprehensible and consistent with the eligibility requirements. Nevertheless, field-testing of the checklists revealed that approximately half (48%) of the respondents felt that one or more questions still needed greater comprehensibility. These findings indicated the need for a checklist guide.In March 2000, WHO convened a meeting of experts to review the medical eligibility criteria for contraceptive use. The article reflects also the resulting updated checklist.